Exosomes purified from a single cell type have diverse morphology. Issue 1 (1st December 2017) - Zabeo, Davide; Cvjetkovic, Aleksander; Lässer, Cecilia; Schorb, Martin; Lötvall, Jan; Höög, Johanna L
ABSTRACT: Extracellular vesicles (EVs) are produced by all known organisms and are important for cell communication and physiology. Great morphological diversity has been described regarding EVs found in body fluids such as blood plasma, breast milk, and ejaculate. However, a detailed morphological analysis has never been performed on exosomes when purified from a single cell type. In this study we analysed and quantified, via multiple electron microscopy techniques, the morphology of exosomes purified from the human mast cell line HMC‐1. The results revealed a wide diversity in exosome morphology, suggesting that subpopulations of exosomes with different and specific functions may exist. Our findings imply that a new, more efficient way of defining exosome subpopulations is necessary. A system was proposed where exosomes were classified into nine different categories according to their size and shape. Three additional morphological features were also found in exosomes regardless of their morphological classification. These findings show that exosomes purified from a single cell line are also morphologically diverse, similar to previous observations for EVs in body fluids. This knowledge can help to improve the interpretation of experimental results and widen our general understanding of the biological functions of exosomes.